Optimalisasi Pengolahan Sampah Dapur melalui Penerapan Losida (Lodong Sisa Dapur) bersama Ibu-Ibu PKK di Dusun Panggang Lele, Desa Arjowilangun, Malang - Anis Shilvi Rahmawati; Tri Gandini Maghfiroh; Yaya Nuraida; Zahrotul Chusna; Adelia Oktaviana; Hauwin Nur Afifah; Indar Parawangsa; M. Rizqi Amurullah; M. Revizal Badrie; Nirina Nasywa Amalia; Tata Savina Cahya (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IAIN Lhokseumawe, 2025)
Kitchen waste that is not properly managed remains an environmental and social issue in many rural areas. One alternative solution is the implementation of the Losida (Lodong Sisa Dapur) method, which emphasizes community participation in organic waste management. This community service program aimed to optimize kitchen waste processing through the application of the Losida method in collaboration with members of the PKK women’s group in Panggang Lele Hamlet, Arjowilangun Village, Malang. The program was conducted using a participatory approach, including socialization activities, hands-on training, and continuous assistance in processing kitchen waste into organic fertilizer at the household level. Evaluation was carried out through observation and monitoring of participants’ involvement and the outcomes of their independent practices. The results indicated an improvement in participants’ understanding and skills in managing organic waste using the Losida method. The organic fertilizer produced demonstrated good quality and was effectively utilized to support household plant productivity. Active participation of the PKK members also encouraged initial behavioral changes in kitchen waste management and opened opportunities for the economic use of organic waste. The implementation of the Losida method proved to be an effective strategy for community empowerment in sustainable kitchen waste management. Therefore, continuous training and community-based assistance are necessary to ensure the long-term sustainability of the program.